2003
DOI: 10.1196/annals.1300.065
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Animal Models of Schizophrenia

Abstract: Several lines of evidence, including recent genetic linkage studies implicating susceptibility genes for schizophrenia, make a strong case that abnormal NMDA receptor-mediated neurotransmission is a major locus for the pathophysiology of schizophrenia. Animal models that are relevant to putative NMDA dysfunction in schizophrenia have excellent face validity for several symptoms of schizophrenia and are important tools for the design of novel pharmacological intervention in schizophrenia. The present chapter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 26 publications
5
76
0
2
Order By: Relevance
“…Our findings that MK-801 produced impairments in performance in two behavioral paradigms related to learning and memory are consistent with previous studies examining the behavioral effects of noncompetitive NMDA receptor antagonists in rodents (Walker and Gold, 1992;Bardgett et al, 2003;Moghaddam and Jackson, 2003). While the circuitry underlying learning and memory in the mammalian brain remains under investigation, proper functioning of the NMDA receptor within the septohippocampal pathway appears to be a critical element of this circuitry (Newcomer and Krystal, 2001).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our findings that MK-801 produced impairments in performance in two behavioral paradigms related to learning and memory are consistent with previous studies examining the behavioral effects of noncompetitive NMDA receptor antagonists in rodents (Walker and Gold, 1992;Bardgett et al, 2003;Moghaddam and Jackson, 2003). While the circuitry underlying learning and memory in the mammalian brain remains under investigation, proper functioning of the NMDA receptor within the septohippocampal pathway appears to be a critical element of this circuitry (Newcomer and Krystal, 2001).…”
Section: Discussionsupporting
confidence: 79%
“…Early support for such hypotheses came from observations that the noncompetitive NMDA receptor antagonist, phencyclidine (PCP), induced a psychosis similar to that observed in patients with schizophrenia (Luisada and Brown, 1976;Allen and Young, 1978). More recently, other noncompetitive NMDA receptor antagonists, such as ketamine and MK-801, have been shown to produce complex syndromes that mimic positive and negative symptoms, as well as the cognitive deficits of schizophrenia (Adler et al, 1999;Buffalo et al, 1994;Moghaddam and Jackson, 2003;Newcomer and Krystal, 2001). Notably, antipsychotic drugs used in the treatment of schizophrenia, such as haloperidol, risperidone, and clozapine, have been shown to block the hyperlocomotion, stereotypies, and ataxia induced by MK-801 in rats (Andine et al, 1999); however, the effects of such drugs on the learning and memory deficits induced by MK-801 in rodents (Bardgett et al, 2003) has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have found that the expression or activity of proteins and genes associated with glutamatergic neurotransmission are altered in schizophrenia patients (Moghaddam, 2003;Tsai et al, 1998). Metabotropic glutamate receptors are involved in regulating neurotransmitter release, including the release of glutamate (Cartmell and Schoepp, 2000), and disorders of the NMDA type of glutamate receptor have been strongly implicated in the etiology of schizophrenia (Moghaddam and Jackson, 2003). In individuals at risk for schizophrenia Egan and colleagues found variations in a particular allele of GRM3, the gene encoding the type 2/3 metabotropic glutamate receptor (mGluR2/3) (Egan et al, 2004).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
“…Traditional models of schizophrenia emphasize the importance of dopaminergic (DA) dysregulation (eg, Davis et al, 1991;Moore et al, 1999), particularly in the etiology of positive symptoms. More recent models, in contrast, emphasize the potential role of N-methyl-D-aspartate (NMDA) receptor dysfunction as a basis for both persistent negative and cognitive symptoms, and DA dysregulation in schizophrenia (Javitt, 1987(Javitt, , 2004Carlsson and Carlsson, 1990;Javitt and Zukin, 1991;Coyle, 1996;Hirsch et al, 1997;Abi-Saab et al, 1998;Olney et al, 1999;Moghaddam and Jackson, 2003). This reconceptualization of schizophrenia has led to efforts both to develop more effective NMDA-stimulating agents, and to define critical sites of interaction between dopamine and NMDA systems.…”
Section: Introductionmentioning
confidence: 99%